The use of abbreviations among UPM international postgraduate students in a WhatsApp study group - Al-Tai, Mahdi Nadhim Baqer; El Kari, Iman (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
The use of English language in WhatsApp study group reflects variations with regard to communicative function and use. Its linguistics features have a specific code when used in mobile-mediated communication among texters. This study aims to identify the variation of use of abbreviations in WhatsApp messaging language between international postgraduates and its communicative functions. The study intended to analyze the use of abbreviations on WhatsApp in terms of their use and communicative function. Herring's (2004) approach of "Computer-Mediated Discourse Analysis" (CMDA) was used to study and identify the use and functions of abbreviations in WhatsApp. Data were collected from WhatsApp chat group of postgraduate students enrolled in a Master’s program at UPM. Numbers of WhatsApp messages were analyzed for the occurrence of abbreviations. The findings of this study showed the communicative functions and use of abbreviations. Finally, this study represents a step toward improved understanding of how technology can better define the nature of human linguistic interaction.